KEPEMIMPINAN KEPALA SEKOLAH DI ERA REVOLUSI INDUSTRI 4.0 DALAM MENINGKATKAN AKREDITASI SEKOLAH - Wulandari, Fitri; Febriansyah, Dwi; Salwa, Salwa; Sulaiman, Raden Muhamad (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The leader is the person who leads. While the leader is his position. In another sense, etymologically the term leadership comes from the basic word